Implementasi Hypnoteaching Dan Neuro Linguistik Programming (NLP) Melalui Pendekatan Teori Maslow Pada Peserta Didik - Nanang Hasan Susanto; Wirda Ramadhanti; Alyan Fatwa (International Journal on Human-Computing Studies, 2021)
This paper aims to explore one of the learning strategies currently developing in the world of education, namely Hypnoteaching through Neuro Linguistic Programming, combined with Abraham Maslow's theory of basic needs. The research method of this paper uses a qualitative approach, by collecting searches of the growing literature on the concept of hypnoteaching, Neuro Linguistic Programming and Maslow's theory of basic needs. The analysis used is discourse analysis and content analysis. This research concludes that the application of Hypnoteaching through Neuro Linguistic Programming which is based on meeting Maslow's basic needs can help students to leave negative habits by improving the subconscious mind program system, so that they can follow the learning process in a relaxed and comfortable manner. Thus, students will find it easier to achieve learning achievement, as well as develop all their potential to the peak of their humanity.